2021
DOI: 10.1051/rees/2021047
|View full text |Cite
|
Sign up to set email alerts
|

Waste to Sustainable Biohydrogen Production Via Photo-Fermentation and Biophotolysis − A Systematic Review

Abstract: Considering the environmental challenges humanity faces in the 21st century, it is obvious that there is an enormous need for change of the global energy map. Under these circumstances, new energy sources and intermediates must be considered as options to limit the greenhouse gases emissions and mitigate climate crisis. Biohydrogen production is one of the most appealing options, due to hydrogen's multiple applications and zero emissions as a fuel, to empower a future hydrogen circular economy. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Photo fermentation was coupled with dark fermentation to convert residue from anaerobic digestion from fish waste into biohydrogen (Melitos et al, 2021). Ghimire et al (2015c) reported that connecting the DF-Photo Fermentation reduces the control of operating parameters such as pH and the process impacts on the energy yield reaching 55 MJ/kg volatile solid food waste, adding a synergistic effect to the overall energy recovery during the conversion of food waste.…”
Section: Biohydrogenmentioning
confidence: 99%
“…Photo fermentation was coupled with dark fermentation to convert residue from anaerobic digestion from fish waste into biohydrogen (Melitos et al, 2021). Ghimire et al (2015c) reported that connecting the DF-Photo Fermentation reduces the control of operating parameters such as pH and the process impacts on the energy yield reaching 55 MJ/kg volatile solid food waste, adding a synergistic effect to the overall energy recovery during the conversion of food waste.…”
Section: Biohydrogenmentioning
confidence: 99%
“…Biophotolysis for hydrogen production is the dissociation or splitting of the water molecule by hydrogenase enzyme under the action of light energy by microorganisms like cyanobacteria and microalgae [26,27].…”
Section: Biophotolysismentioning
confidence: 99%
“…The first phase is a light-dependent-phase aerobic process, where the microbes synthesize carbohydrates from water and carbondioxide using light energy (Equation (3)). In aerobic conditions with the supply of air, the biomass progressively increases and is concentrated until it reaches a state of stabilization [26,31].…”
Section: Indirect Biophotolysismentioning
confidence: 99%
“…Pyrolysis and gasification of materials such as grass, straw, or biological waste are possible thermochemical routes. Alternatively, biophotolysis, based on the biological gas conversion and fermentation reactions, may also be applied [97][98][99]. In water electrolysis, on the other hand, an electric current is used to separate water into hydrogen and oxygen.…”
mentioning
confidence: 99%
“…This production process achieves efficiencies of up to 70% [82]. In proton exchange membrane (PEM) electrolysis, the protonconducting membrane serves as the electrolyte, and the efficiency of this process is about 50% [99].…”
mentioning
confidence: 99%